Clinical Efficacy and Determinants of Response to Treatment with Desmopressin in Mild Hemophilia A - Di Perna, Caterina; Riccardi, Federica; Franchini, Massimo; Rivolta, Gianna Franca; Pattacini, Corrado; Tagliaferri, Annarita (Seminars in Thrombosis and Hemostasis, 2013)
Although desmopressin (DDAVP) is considered as the treatment of choice for many patients with mild hemophilia A, several aspects of DDAVP therapy remain unclear, including the rate and type of response and the molecular determinants of its clinical efficacy. To investigate these issues, we retrospectively studied all patients with mild hemophilia A followed up at the Parma Hemophilia Center. A total of 75 patients were enrolled who underwent a DDAVP test, and out of whom, 76% (57/75) had a complete or partial response. Response to DDAVP was significantly correlated to the patients' age (median age of responders and nonresponders: 24 and 18 y, respectively; p = 0.04) and type of mutation (all the 10 patients with mutations in the promoter region were nonresponders). The median basal factor VIII (FVIII):C level was significantly lower in responders than in nonresponders (0.14 vs. 0.19 IU/mL, respectively; p = 0.01); this was mainly due to nonresponders with promoter region mutations who had higher basal FVIII:C levels. During the 12-year follow-up, 82 of 237 (35%) bleeding episodes occurring in 27 responder patients were treated with 246 DDAVP infusions with complete or partial efficacy in 92% (75/82). Overall, 142 events were managed with 253 prophylactic DDAVP infusions, which were hemostatically effective in 96% of cases. No severe adverse reactions to DDAVP administration were recorded during the study period. These results document the safety and efficacy of DDAVP as a treatment or prevention of bleeding in patients with mild hemophilia A, also in the context of home treatment, and encourage the more widespread use of this product.
Keywords: mild hemophilia A; desmopressin; treatment efficacy; genotype